Treatment Patterns and Health Outcomes in Platinum-Refractory or Platinum-Resistant Ovarian Cancer: A Retrospective Medical Record Review. Issue 4 (May 2018) - Parikh, Rohan; Kurosky, Samantha K.; Udall, Margarita; Chang, Jane; Cappelleri, Joseph C.; Doherty, Jim P.; Kaye, James A.
Abstract : Objective: The objective of this article is to describe real-world treatment patterns and outcomes in patients with platinum-refractory/resistant epithelial ovarian, fallopian tube, or primary peritoneal cancer (PRROC) in the United States, United Kingdom, and Canada. Methods/Materials: Physicians retrospectively reviewed medical records of women aged 18 years or older who were diagnosed with PRROC between January 2010 and June 2014. Patient characteristics, initial PRROC therapy, and health care utilization were assessed; progression-free survival (PFS) and overall survival were estimated using Kaplan-Meier and Cox proportional hazards methods. Results: Data were obtained on 392 US, 296 UK, and 82 Canadian patients. At initial ovarian cancer diagnosis, 65.8% (United States), 93.3% (United Kingdom), and 82.9% (Canada) of patients had stage III/IV disease; 43.6%, 73.7%, and 56.1%, respectively, had high-grade tumors. At PRROC diagnosis, mean age was 57.2 years (United States), 59.2 years (United Kingdom), and 57.4 years (Canada). Eastern Cooperative Oncology Group performance status was 0/1 at PRROC diagnosis for 57.7% (United States), 80.1% (United Kingdom), and 36.6% (Canada) of patients. Most patients initiated systemic treatment after PRROC diagnosis (United States, 71.4%; United Kingdom, 83.1%; Canada, 81.7%). The most common initial PRROC therapy was pegylated liposomal doxorubicin monotherapy (United States, 18.6%; United Kingdom, 50.0%; Canada, 34.3%). During initial PRROC treatment, 80.7%, 59.8%, and 44.8% of patients had 1 office visit or more and 17.5%, 10.2%, and 14.9% of patients had 1 hospitalization or more in the United States, the United Kingdom, and Canada, respectively. Treatment toxicity was the most common reason for hospitalization (United States, 75.5%; United Kingdom, 64.0%; Canada, 80.0%). Median (95% confidence interval) PFS was 5.6 (4.9–6.2), 8.0 (6.8–9.2), and 6.4 (5.4–9.3) months in the United States, the United Kingdom, and Canada. The Cox proportional hazards model showed that stage III/IV, high-grade tumors, and poorer performance status were associated with shorter survival. Conclusions: Current treatments for PRROC yield limited PFS and frequent hospitalizations reported to be related to toxicities or procedural complications, suggesting a continued unmet need for more effective and tolerable therapeutic strategies for PRROC. Abstract : Supplemental digital content is available in the text.